Analisis Beban Kerja Mental Pada Pekerja Di Industri Pembuatan Tempe - Hardik Widananto; Diyah Dwi Nugraheni (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2019)
Company X is a SME company that produced tempe, activity that is examined in the production process of Tempe is soybean washing activity, basket lifting and packaging. The purpose of this research is to determine the mental workload on the operators who carried out production activities. This research used the NASA-TLX method with the indicator of mental demand (MD), physical demand (PD), temporal demand (TD), performance (P), effort (E), and frustration level (FR). Data processing results show that soybean washing activity has a NASA-TLX score of 88, the basket lifting activity has a score of 88.67, and the packaging activity has a score of 90. The score shows that the workload on soybean washing activity, basket lifting, and packaging is very high for the operator. From these results, it is necessary to repair the working system so that the operator's mental workload can decrease so as to improve the operator's productivity and health.